2011
DOI: 10.1007/s00706-011-0551-1
|View full text |Cite
|
Sign up to set email alerts
|

An environmentally benign procedure for the synthesis of substituted 2-thiobenzothiazoles, 2-thiobenzoxazoles, 2-thiobenzimidazoles, and 1,3-oxazolopyridine-2-thiols

Abstract: An improved method for the synthesis of the title compounds is presented which uses glycerol or PEG 400 as solvent under microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The following descriptors were predicted: Central nervous system (CNS) activity (from -2 for inactive to +2 for active); octanol/water partition coefficient, logPo/w (-2.0 to 6.5); IC 50 value for the block of HERG K + channels, log HERG (concern < −5); Caco-2 cell membrane permeability in nm s -1 , PCaco (: < 5 low to > 100 high); logarithm of the predicted blood/brain barrier partition coefficient, log B/B (-3.0 to 1.0); apparent Madin-Darby canine kidney cell permeability (PMDCK ) that mimic the blood-brain barrier for non-active transport in nm s -1 , PMDCK (< 25 poor to > 500 great); skin permeability, log K p (−8.0 to −1.0); logarithm of binding constant to human serum albumin, log K HSA (-1.5 to 1.2); qualitative human oral absorption (HOA) (1: low, 2: medium, 3: high); percent of HOA (>80%: high, <25%: poor) ( Table 2). H-NMR spectra of the compounds showed that the protons belonging to the 6-benzoylbenzo[d] thiazole-2(3H)-thione ring system exhibited similar properties to those reported by previous studies 15,29 . All the other protons were observed according to the expected chemical shift and integral values.…”
Section: Prediction Of Drug-likeness Molecular and Adme Propertiessupporting
confidence: 80%
“…The following descriptors were predicted: Central nervous system (CNS) activity (from -2 for inactive to +2 for active); octanol/water partition coefficient, logPo/w (-2.0 to 6.5); IC 50 value for the block of HERG K + channels, log HERG (concern < −5); Caco-2 cell membrane permeability in nm s -1 , PCaco (: < 5 low to > 100 high); logarithm of the predicted blood/brain barrier partition coefficient, log B/B (-3.0 to 1.0); apparent Madin-Darby canine kidney cell permeability (PMDCK ) that mimic the blood-brain barrier for non-active transport in nm s -1 , PMDCK (< 25 poor to > 500 great); skin permeability, log K p (−8.0 to −1.0); logarithm of binding constant to human serum albumin, log K HSA (-1.5 to 1.2); qualitative human oral absorption (HOA) (1: low, 2: medium, 3: high); percent of HOA (>80%: high, <25%: poor) ( Table 2). H-NMR spectra of the compounds showed that the protons belonging to the 6-benzoylbenzo[d] thiazole-2(3H)-thione ring system exhibited similar properties to those reported by previous studies 15,29 . All the other protons were observed according to the expected chemical shift and integral values.…”
Section: Prediction Of Drug-likeness Molecular and Adme Propertiessupporting
confidence: 80%
“…83-91% yield 2-aminophenols, 2-aminothiophenols, 1,2-diaminobenzenes, or 2amino-3-hydroxypyridines with potassium O-ethyl dithiocarbonate in glycerol under microwave irradiation (Scheme 11). 27 The best yields are obtained when the reaction mixture is irradiated for 5 min at 30 W or for 2 min at 45 W.…”
Section: Scheme 9 Non-catalyzed Synthesis Of 1h-benzodiazepines and Bmentioning
confidence: 99%
“…The reactive intermediate 2,4‐dichloroquinazoline ( 1 ) was obtained by the reaction of substituted anthranilic acid with urea followed by chlorination with POCl 3 in the presence of a base . The compounds benzo[ d ]oxazole‐2‐thiol ( 2 ), benzo[ d ]thiazole‐2‐thiol ( 3 ), and 1 H ‐benzo[ d ]imidazole‐2‐thiol ( 4 ) were prepared by the reaction of 2‐aminophenol/2‐aminothiophenol/ o ‐phenylenediamine with CS 2 in the presence of KOH in ethanol . The compounds benzo[ d ]oxazol‐2‐amine ( 5 ), benzo[ d ]thiazol‐2‐amine ( 6 ), and 1 H ‐benzo[ d ]imidazol‐2‐amine ( 7 ) were obtained by the reaction of respective o ‐disubstituted benzenes with cyanogen bromide in ethanol .…”
Section: Resultsmentioning
confidence: 99%